2016
DOI: 10.15288/jsad.2016.77.337
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alcohol-Related Personalized Normative Feedback With and Without an Injunctive Message

Abstract: ABSTRACT. Objective: Personalized normative feedback (PNF) has been used extensively to reduce alcohol consumption, particularly among heavy drinkers. However, the majority of PNF studies have used only descriptive norms (real or perceived pervasiveness of a given behavior). The purpose of the current study was to explore the efficacy of PNF both with and without an injunctive message indicating approval or disapproval based on the participants' standing relative to other students' drinking levels. This random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Overall, there were 53 studies targeting alcohol, three studies targeting cannabis, and four studies targeting both alcohol and cannabis that reported sufficient effect size data to be included in the meta‐analyses. In 18 of the studies (Andersson, 2015; Bernstein, 2016; Butler, 2009; Cunningham, 2015; Gajecki, 2014; Kypri, 2008; LaBrie, 2013; Lewis, 2007; Murphy, 2010 study 2; Rocha, 2013; Steers, 2016; Suffoletto, 2012; Suffoletto, 2014; Wagener, 2012; Weaver, 2014; Witkiewitz, 2014; Christoff, 2015; Walton, 2013), there was more than one intervention group. We included the comparisons that were pre‐planned, and we specified the comparison condition for each included study in the Characteristics of Included Studies table ().…”
Section: Resultsmentioning
confidence: 99%
“…Overall, there were 53 studies targeting alcohol, three studies targeting cannabis, and four studies targeting both alcohol and cannabis that reported sufficient effect size data to be included in the meta‐analyses. In 18 of the studies (Andersson, 2015; Bernstein, 2016; Butler, 2009; Cunningham, 2015; Gajecki, 2014; Kypri, 2008; LaBrie, 2013; Lewis, 2007; Murphy, 2010 study 2; Rocha, 2013; Steers, 2016; Suffoletto, 2012; Suffoletto, 2014; Wagener, 2012; Weaver, 2014; Witkiewitz, 2014; Christoff, 2015; Walton, 2013), there was more than one intervention group. We included the comparisons that were pre‐planned, and we specified the comparison condition for each included study in the Characteristics of Included Studies table ().…”
Section: Resultsmentioning
confidence: 99%
“…Together, the results from Latimer and colleagues' (2011) study and ours suggest that interventions targeting normative misperceptions among women in jail may need to provide feedback based on participant group membership that includes similarity as to which substance‐related disorders are of concern. In addition, interventions may need to consider not only descriptive norms (estimates of substance use behaviors) as the present study did but also injunctive norms (the approval of substance use) by the selected reference groups, as injunctive norms were positively associated with drinking behavior among college students in some studies (e.g., Lee et al, 2007) although not others (e.g., Steers et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their early promise, these approaches have generally been found to be ineffective (Foxcroft, Moreira, Almeida Santimano, & Smith, 2015), although they are still prevalent (Miller et al, 2013). Including injunctive information in interventions that present personalized normative feedback to at-risk students may have promise (Dotson, Dunn, & Bowers, 2015), but finding ways to present this normative information without raising resistance is an important task for future research (Steers et al, 2016).…”
Section: Discussionmentioning
confidence: 99%